2018
DOI: 10.1111/jphp.13012
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of potent anticarcinogenic activity of 1, 3-diarylpyrazole acrylamide derivatives in vitro

Abstract: 4k has revealed its potent antiproliferative activity by decreasing viability and inhibiting proliferation and survival signals of cancer cells. Moreover, 4k has exposed cytostatic and apoptotic effect especially, on cancer cells. Therefore, it may be necessary to examine the biological actions of 4k in vivo as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Demiroglu-Zergeroglu et al studied the in vitro potential anticancer activity of a series of 1,3-diarylpyrazole acrylamide derivatives against mesothelial cells (MeT-5a), malignant mesothelioma (SPC212), and lung cancer cell lines (A549). Among all the synthesized derivatives, compound 40 ( Figure 4 for structures of compounds 40 – 43 ) revealed excellent antiproliferative activity [ 63 ]. Further evaluation showed that compound 40 could trigger caspase-dependent apoptosis in SPC212 cells and significantly inhibit the phosphorylation and expression of ERK1/2 and AKT proteins at concentrations above 10 µM in 24 h. In addition, compound 40 could induce G2/M cell arrest in a dose- and cell-dependent manner, with SPC212 cells being more susceptible than A549 cells.…”
Section: Kinase Inhibitorsmentioning
confidence: 99%
“…Demiroglu-Zergeroglu et al studied the in vitro potential anticancer activity of a series of 1,3-diarylpyrazole acrylamide derivatives against mesothelial cells (MeT-5a), malignant mesothelioma (SPC212), and lung cancer cell lines (A549). Among all the synthesized derivatives, compound 40 ( Figure 4 for structures of compounds 40 – 43 ) revealed excellent antiproliferative activity [ 63 ]. Further evaluation showed that compound 40 could trigger caspase-dependent apoptosis in SPC212 cells and significantly inhibit the phosphorylation and expression of ERK1/2 and AKT proteins at concentrations above 10 µM in 24 h. In addition, compound 40 could induce G2/M cell arrest in a dose- and cell-dependent manner, with SPC212 cells being more susceptible than A549 cells.…”
Section: Kinase Inhibitorsmentioning
confidence: 99%
“…[25] Concerning the nitro chalcones, an increase in the interactions with the protein residues in the VEGFR-2 active site was detected when the nitro group was present in the α,β-unsaturated carbonyl system. [26] Some pyrazole chalcones were reported to be effective against HELA and MCF-7 cancer cells, [27] whereas pyrazole-based chalcones 7 and 8 were effective against leukaemia cell lines. [28,29] Chalcones can suppress cancer cells through a variety of methods, including tubulin inhibition, [30] cyclin-dependent kinase (CDK(, [31] vascular endothelial growth factor receptor-2 (VEGFR-2), [32] epidermal growth factor receptor (EGFR), [33] glycogen synthase kinase 3 beta (GSK3β), [34] and mitogen-activated protein kinase (MAPK), [35] which is a common serine and threonine protein kinase found in eukaryotes, [36] and is critical for conveying extracellular stimuli into cells and inducing biological responses that can impact cell proliferation, differentiation, apoptosis, inflammation, and other processes.…”
Section: Introductionmentioning
confidence: 99%